Effects of systemic inflammation and frailty on survival in elderly cancer patients: Results from the INSCOC study - Zhang, Qi; Wang, Ziwen; Song, Mengmeng; Liu, Tong; Ding, Jiashan; Deng, Li; Zhang, Xi; Qian, Liang; Ge, Yizhong; Xie, Hailun; Ruan, Guotian; Song, Chunhua; et al. (Frontiers in Immunology, 2023)
Background Frailty and systemic inflammation are parameters, which are easy to evaluate, can be used to predict disease outcomes, and are potentially modifiable. The combination of frailty and inflammation-based data may help identify elderly cancer patients predisposed to adverse clinical outcomes. The aim of this study was to examine the association of systemic inflammation and frailty at admission, and to determine whether these risk factors interact and may predict the survival of elderly cancer patients. Methods A prospective Investigation on Nutrition Status and Clinical Outcome of Common Cancers (INSCOC) with 5,106 elderly cancer patients admitted from 2013 through 2020 was included in this study. The primary marker of inflammation was the neutrophil-to-lymphocyte ratio (NLR), with the reference group having NLR<3, which indicated no inflammation. Frailty was assessed using the FRAIL scale, and patients with≥3 positives out of a total of five components were assumed to be frail. The primary outcome was all-cause mortality. We classified participants according to the presence (or absence) of frailty and high inflammation and assessed their association with overall survival using the Cox proportional hazards models adjusted for demographic, tumor, and treatment factors. Results Among the 5,106 patients enrolled in the study, 3396 individuals (66.51%) were male and the mean( ± SD) age at diagnosis was 70.92( ± 5.34). Over a median of 33.5 months follow-up, we observed 2,315 deaths. Increasing NLR was associated with frailty (compared with NLR<3, odds ratio=1.23, 95%CI=1.08-1.41 for NLR≥3). An NLR≥3 and frailty independently predicted the overall survival [hazard ratio(HR)=1.35, 95%CI=1.24-1.47 and HR=1.38, 95%CI=1.25-1.52, respectively). Patients with both frailty and NLR≥3 had the lowest overall survival(HR=1.83, 95%CI=1.59-2.04) than patients with no risk factors. The mortality rate increased with the presence of the frailty components. Conclusions Systemic inflammation was positively associated with frailty. Frail elderly cancer patients with elevated systemic inflammation had low survival rate.